Lived Experiences of Teachers in Handling Learners with Autism Spectrum Disorder: Input for A Training Program - Uy, Keinrich Ace; Florendo, Helena (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored the experiences of elementary school teachers in implementing inclusive education for learners with Autism Spectrum Disorder (ASD) in mainstream classrooms in Santiago City, Isabela. Anchored on Bronfenbrenner’s Ecological Systems Theory (1979), the research examined instructional strategies, teacher preparedness, stakeholder support, and challenges encountered in integrating learners with ASD into regular classroom settings. The study employed a qualitative descriptive phenomenological design involving elementary teachers from Santiago South Central School and Santiago North Central School during the School Year 2025–2026. Purposive sampling was used to select participants with direct experience teaching learners with ASD. Data were gathered through questionnaires, focus group discussions, semi-structured interviews, and classroom observations. The instruments underwent expert validation, while reliability testing yielded a Cronbach’s alpha score of 0.70. Qualitative data were analyzed through thematic analysis using Taguette software. Findings revealed that teachers utilized structured routines, visual supports, differentiated instruction, positive reinforcement, and visual scheduling to support learners with autism in inclusive classrooms. However, teachers experienced significant challenges related to insufficient training, limited instructional materials, difficulties in assessment practices, and inconsistent stakeholder support. The study also found that collaboration among parents, administrators, and government institutions contributed positively to inclusive education, although operational and resource limitations remained evident. To address these concerns, the study proposed the CARES action plan aimed at strengthening teacher capacity, instructional support, stakeholder collaboration, and inclusive classroom practices. The study aligns with Sustainable Development Goal (SDG) 4: Quality Education by promoting inclusive and equitable learning opportunities for learners with disabilities. It also supports SDG 10: Reduced Inequalities through advocacy for equitable access and participation in education for learners with ASD. The study contributes to educational and institutional sustainability by promoting stronger support systems, continuous teacher development, and collaborative inclusive education practices that foster equitable and supportive learning environments.
Keywords: Assessment Practices; Autism Spectrum Disorder (ASD); Differentiated Instruction; Inclusive Education; Stakeholder Support; Structured Routines; Teacher Preparedness; Visual Supports